PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS LIVE WORKSHEET UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS V - Auliya Dwi Cahyani; Encep Andriana; A. Syachruroji (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
To find out the development, student responses, feasibility and concept mastery of students in the use of Live Worksheet-based LKPD for thematic learning themes 9 sub-themes 2 class V at SD Islam Modern An-Nur, the research method used in this development research is Sugiyono's modification includes 6 steps, namely problem analysis, data collection, product design, design validation, design revision and product testing.The subject of this study was An-Nur Modern Islamic Elementary School with 15 students in class V. The data collection tools used were expert validation questionnaires, student response questionnaires as well as pretest and posttest. The data analysis technique used in this research is descriptive analysis.. The measurement scale that will be used in this study to determine the score of the respondents' answers is to use the Guttman Scale. The tests carried out are by using pretest and posttest. The results of this study obtained the feasibility of a team of media and material experts as much as 89% (Very Eligible). Student responses to live worksheet-based student worksheets obtained an average student response of 96% which, based on the interpretation category, was included in the "very good" category. good". Mastery of students' concepts of Live Worksheet-based Student Worksheets can be seen through the pretest and posttest that have been carried out. From the results of the pretest, the percentage of the average value is 5, while after the posttest, the average value is 8, which is based on the category of interpretation included in the category of "very feasible". Based on these results, student worksheets based on live worksheets can increase student activity and learning outcomes.